Dynamic Neuroimmune Profile during Mid-life Aging in the Female Brain and Implications for Alzheimer Risk - Aarti Mishra; Yuan Shang; Yiwei Wang; Eliza R. Bacon; Fei Yin; Roberta D. Brinton (iScience, 2020)
Summary: Aging and endocrine transition states can significantly impact inflammation across organ systems. Neuroinflammation is well documented in Alzheimer disease (AD). Herein, we investigated neuroinflammation that emerges during mid-life aging, chronological and endocrinological, in the female brain as an early initiating mechanism driving AD risk later in life. Analyses were conducted in a translational rodent model of mid-life chronological and endocrinological aging followed by validation in transcriptomic profiles from women versus age-matched men. In the translational model, the neuroinflammatory profile of mid-life aging in females was endocrine and chronological state specific, dynamic, anatomically distributed, and persistent. Microarray dataset analyses of aging human hippocampus indicated a sex difference in neuroinflammatory profile in which women exhibited a profile comparable to the pattern discovered in our translational rodent model, whereas age-matched men exhibited a profile consistent with low neuroimmune activation. Translationally, these findings have implications for therapeutic interventions during mid-life to decrease late-onset AD risk.